Analisis Keterampilan Membaca Permulaan Pada Siswa Kelas 2 di SDN 4 Paduraksa - Tilaras, Sekar Anggun; Ysh, A. Y Soegeng; Setianingsih, Eka Sari (STKIP Andi Matappa Pangkep, 2024)
This research aims to determine students' initial reading skills by analyzing the learning process and the factors that cause students' low reading competence. The type of research used is descriptive qualitative research. The subject of this research was a class 2 students at SDN 04 Paduraksa who had difficulty reading at the beginning. Data collection techniques use observation, interviews and documentation. The validity of the data in this research is source triangulation. The data analysis technique uses interactive model data analysis, namely data collection, data reduction, and conclusion/verification. The results of this research are based on observations and interviews of class 2 teachers at SDN 04 Paduraksa, showing that it is known that one of the class 2 students is having difficulty reading at the beginning. During class hours or extra hours, one of the students could not string letters into words and could not put words into sentences. What caused the initial reading difficulties experienced by one of these students were psychological factors which made the students less interested in reading, lazing around, not focusing on attending lessons or extra hours and environmental factors which resulted in lack of parental attention and lack of support for learning to read.